Pengaruh Job Insecurity Dan Stres Kerja Terhadap Turnover Intention Karyawan Outsourcing Pada PT Gokko Mirai Indonesia - Febriyanti, Riski; Marliani, Sari; Yuliawati, July (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Research conducted at PT Gokko Mirai Indonesia which is located on Jl. Subang Blok C No.1, Karangpawitan, Kec. West Karawang, Karawang, West Java 41315 aims to identify, analyze and explain job insecurity, work stress and turnover intention. The research method uses descriptive and verification through a quantitative approach, with multipleelinear regression analysis using SPSS. The sample consisted of 105 outsourcing employees in total who were randomly selected through a simple random sampling technique. The results of this study show 1) The job insecurity score of 412 is in the high category. 2) A work stress score of 417 is intthe high category. 3) a turnover intention score of 422 is in the high category. 4) The sig value of job insecurity is 0.227>0.05 and the t-count is 1.215<1.983, meaning that job insecurity has no partial effect on turnover intention. 5) The sig value of work stress is 0.000 <0.05, t-count 8.497 <1.983, meaning that work stress has a partially significant effect on turnover intention. 6) The turnover intention sig value is 0.000 <0.05, f-count 111.218>3.08, meaning that job insecurity and work stress simultaneously have a significant effect on turnover intention. The R square value of 0.686 shows that these two variables influence 68.6% of turnover intention, and the remaining 31.4% can be influenced by other variables that researchers didnnot carefully examine.